Emission spectroscopy of an atmospheric pressure plasma - Asenjo-Castillo, José (2016)
Recently atmospheric pressure plasmas have become a topic of great interest for a wide range of applications in different branches of industry. In order to ensure that the industrial and technological applications of plasmas are being carried out with a maximum of efficiency it is necessary to know and control the processes that take place in the plasmas during their application which is strongly associated with densities and temperatures of different plasma species such as electron and heavy particles. In this work are presented the results of the research focuses on the use of optical emission spectroscopy technique to study some parameters of high pressure plasmas.